High-toughness heat-conducting structure bonding organopolysiloxane composition and preparation method thereof
By using reactive silanoxy-terminated polymers and cyclic polysiloxane bonding promoters in thermal fillers, a tight chemical action and cross-linking network is formed, and the reliability of thermal composite materials in high temperature and high humidity environments is solved. The problem of insufficient has achieved high toughness, high thermal conductivity and high reliability bonding applications of thermal management systems.
Patent Information
- Application Number
- CN202411294821.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-14
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2044-09-14
AI Technical Summary
The existing surface treatment technology of thermally conductive fillers is difficult to improve the compatibility and mechanical properties of inorganic fillers and organic resins at the same time, resulting in insufficient reliability of thermally conductive composite materials in high temperature and high humidity environments.
Reactive silanoxy-terminated polymer (RST) and cyclic polysiloxane bonding promoters are used as treatment agents for thermal fillers and interface bonding promoters to enhance composite materials by forming a tight chemical action and cross-linking network. Mechanical toughening and high temperature and humidity resistance.
It realizes the bonding application of thermal management system with high toughness, high thermal conductivity and high reliability, improves the mechanical properties and high temperature and humidity resistance of composite materials, and is suitable for applications such as integrated circuit packaging chip heat dissipation frames.
Smart Images

Figure QLYQS_1 
Figure BDA0005045611490000021 
Figure BDA0005045611490000051
Abstract
Description
Technical field:
[0001] The invention relates to a high-toughness heat-conducting structure bonding organic polysiloxane composition and a preparation method thereof, and belongs to the field of heat curing, bonding sealing and heat dissipation solution. Background technology:
[0002] Silicone materials have excellent heat resistance, cold resistance, dielectric properties, ozone resistance and atmospheric aging resistance, and have a wide operating temperature range. They can be used for a long time at -60°C (or lower temperatures) to +250°C (or higher temperatures). They have gained widespread attention and application in all walks of life, especially in the thermal interface material industry. Silicone thermal interface materials have occupied a major position, including thermal grease, thermal silicone gel, thermal adhesive silicone, etc.
[0003] For thermally conductive silicon materials, the surface treatment technology of thermally conductive fillers has always been one of the key technologies that industry workers are most concerned about, because through the surface treatment technology of thermally conductive fillers, the following major problems can be solved: effectively reduce the viscosity after filling, so that the filling amount of thermally conductive fillers can be effectively increased, thereby improving the thermal conductivity; effectively improve the compatibility between inorganic fillers and organic resins, thereby improving the reliability of thermally conductive composite materials. However, under the action of most treatment agents, although it can effectively improve the compatibility between inorganic fillers and organic resins and reduce the viscosity of thermally conductive products, it is often because there is no chemical bond between the treatment agent and the resin system. In most cases, the mechanical properties of the product are often adversely affected.
[0004] The present invention aims to introduce a treatment agent using a reactive silaneoxy-terminated polymer (RST) as a thermally conductive filler, which can effectively achieve the above two treatment purposes on the one hand, and at the same time, the reactive functional group enables RST to participate in the formation of the cross-linked network of the overall organic material, and by means of a close chemical reaction between RST and the thermally conductive filler, both components of RST and the thermally conductive filler can effectively improve the mechanical toughening of the composite material, and at the same time, the thermally conductive composite material can still have excellent high temperature and high humidity resistance even if the easily hydrolyzed aluminum nitride material is used. With the help of the role of the cyclic polysiloxane adhesion promoter, the structural bonding application requirements of the thermal management system with high toughness, high thermal conductivity and high reliability can be effectively achieved. Summary of the invention:
[0005] The purpose of the present invention is to provide a high-toughness thermal conductive structure bonding organic polysiloxane composition and a preparation method thereof, which is suitable for thermal management system bonding applications requiring high toughness, high thermal conductivity and high reliability, such as integrated circuit packaging chip heat dissipation frame bonding, etc. The present invention adopts reactive siloxy-terminated polymer (RST) and cyclic polysiloxane adhesion promoter as a treatment agent for thermal conductive fillers and a promoter for interfacial bonding, respectively. On the one hand, the functions of traditional thermal conductive filler treatment agents and interfacial bonding promoters can be realized: increasing the interfacial compatibility of organic and inorganic materials, reducing viscosity and promoting interfacial bonding; on the other hand, these two major components can participate in the formation of a cross-linked network of the overall organic material, so that the inorganic filler and the annular structure effectively become a reinforcing and toughening structure of the composite material, which is helpful for the mechanical toughening of the composite material. At the same time, the present invention discloses a suitable treatment process for thermal conductive fillers and a preparation method for the composition, which helps RST to form a close chemical reaction with the thermal conductive filler, and effectively improves the high temperature and high humidity resistance of the composite material.
[0006] The high-toughness thermally conductive structure bonding organopolysiloxane composition of the present invention comprises at least the following components (A)-(F):
[0007] (A) 5-35 parts of an organosiloxane polymer having 2 or more alkenyl groups per molecule;
[0008] (B) 0.1-10 parts of an organosiloxane polymer having 2 or more Si-H bonds per molecule;
[0009] (C) 0.05-5 parts of reactive siloxy-terminated polymer (RST);
[0010] (D) 55-95 parts of thermally conductive filler;
[0011] (E) 0.05-2 parts of annular polysiloxane adhesion promoter;
[0012] (F) 0.01-1 part of platinum catalyst;
[0013] The component (A) is an organosiloxane polymer having 2 or more alkenyl groups per molecule, and its general structural formula is (R 1 R 2 2 SiO 1 / 2 )(R 1 R 2 SiO 2 / 2 ) a (R 2 SiO 3 / 2 ) b (SiO 4 / 2 ) c , where R 1 , R 2Each independently represents an unsubstituted or substituted monovalent hydrocarbon group. As the monovalent hydrocarbon group, a group having 1 to 10 carbon atoms, particularly preferably 1 to 6 carbon atoms, specifically, lower alkyl groups such as methyl, ethyl, propyl, isopropyl, cycloalkyl groups such as cyclohexyl, aryl groups such as phenyl, tolyl, xylyl, aralkyl groups such as benzyl, alkane groups containing olefinic bonds such as vinyl and propenyl, or groups in which some or all of the hydrogen atoms of the above groups are replaced by halogen atoms, cyano groups, etc., such as chloromethyl and cyanoethyl. More preferably, it is preferably selected from groups such as methyl, ethyl, vinyl, phenyl, etc., and R 1 and R 2 At least one of the groups is vinyl. a=0~180 (excluding 0), b=0~2, c=0~2, a+b+c=1~180.
[0014] The component (B) is an organosiloxane polymer having 2 or more Si-H bonds per molecule, and its general structural formula is (R 1 R 2 2 SiO 1 / 2 )(R 1 R 2 SiO 2 / 2 ) m (R 2 SiO 3 / 2 ) n (SiO 4 / 2 ) x , where R 1 , R 2 Each independently represents an unsubstituted or substituted monovalent hydrocarbon group. As the monovalent hydrocarbon group, a group having 1 to 10 carbon atoms, particularly preferably 1 to 6 carbon atoms, specifically, lower alkyl groups such as methyl, ethyl, propyl, isopropyl, cycloalkyl groups such as cyclohexyl, aryl groups such as phenyl, tolyl, xylyl, aralkyl groups such as benzyl, alkane groups containing olefinic bonds such as vinyl and propenyl, or groups in which some or all of the hydrogen atoms of the above groups are replaced by halogen atoms, cyano groups, etc., such as chloromethyl and cyanoethyl. More preferably, it is preferably selected from groups such as methyl, ethyl, and phenyl, and R 1 and R 2 At least one of the groups is H. m=0~35, n=0~2, c=0~0.5, m+n+c=1~35.
[0015] The component (C) is a reactive siloxy-terminated polymer (RST), and its structure is as follows:
[0016]
[0017] Among them, R 1 , R 2Each independently represents an unsubstituted or substituted monovalent hydrocarbon group. As a monovalent hydrocarbon group, a group having 1 to 10 carbon atoms, particularly preferably 1 to 6 carbon atoms, specifically, methyl, ethyl, propyl, isopropyl and other lower alkyl groups, cyclohexyl and other cycloalkyl groups, phenyl, tolyl, xylyl and other aryl groups, benzyl and other aralkyl groups, vinyl, propenyl and other olefinic alkyl groups, or groups in which some or all of the hydrogen atoms of the above groups are replaced by halogen atoms, cyano and the like, such as chloromethyl, cyanoethyl and the like. More preferably, groups selected from methyl, ethyl, phenyl and the like are preferred. R3 is a reactive active group that can participate in hydrosilylation, such as vinyl, propenyl and other olefinic alkyl groups, or H and the like. y 1 ,y 2 ,y 3 ,y 4 are independent of each other and can be integers from 0 to 50, and y 1 +y 2 +y 3 +y 4 =0~50.
[0018] The thermal conductive filler of component (D) is a common thermal conductive filler on the market, such as aluminum oxide, aluminum hydroxide, aluminum nitride, aluminum powder, etc., and one thermal conductive filler can be used alone, or different thermal conductive fillers can be used in combination. There is no special requirement for the morphology of the thermal conductive filler, which can be spherical, or irregularly shaped blocks or sheets. The maximum particle size of the thermal conductive filler does not exceed 80um.
[0019] The component (E) cyclic polysiloxane adhesion promoter, "cyclic" comes from cyclic polysiloxane, is a ring body of 4-8 Si-O segments, one side of the Si atom is a monovalent hydrocarbon group such as methyl, ethyl, propyl, isopropyl, etc., and the other side can be a polar group containing siloxane group, epoxy group, acyloxy group and the like that plays a role in promoting adhesion, or a monovalent hydrocarbon group such as methyl, ethyl, propyl, isopropyl, vinyl, propenyl and H, and one molecule of cyclic polysiloxane adhesion promoter must contain 2 or more polar groups containing siloxane group, epoxy group, acyloxy group and the like that play a role in promoting adhesion, and must contain 1 or more reactive active groups such as vinyl, propenyl and H that can participate in hydrosilylation.
[0020] The platinum catalyst of component (F) is one or a mixture of platinum chloride, alcohol-modified platinum chloride, a complex of platinum chloride and diene, a platinum-olefin complex, a platinum-carbonyl complex such as platinum bis(acetoacetate) or platinum bis(acetylacetone), a platinum chloride-alkenylsiloxane complex such as platinum chloride-divinyltetramethyldisiloxane complex or platinum chloride-tetravinyltetramethylcyclotetrasiloxane, a platinum-alkenylsiloxane complex such as platinum-divinyltetramethyldisiloxane complex or platinum-tetravinyltetramethylcyclotetrasiloxane, a complex between platinum chloride and acetylene alcohol, and a capsule-type platinum catalyst.
[0021] The preparation method of the high-toughness thermal conductive structure bonding organic polysiloxane composition of the present invention is divided into two parts. The first step is the pretreatment of the thermal conductive filler, and the second step is the preparation of the high-toughness thermal conductive structure bonding organic polysiloxane composition.
[0022] The process of pretreatment of thermal conductive filler is as follows: weigh component (A) organic siloxane polymer with 2 or more alkenyl groups per molecule and component (C) reactive siloxy-terminated polymer (RST), mix and stir evenly, add a certain amount of ethanol solution of deionized water (the content of deionized water is 1‰ to 10%), and stir and mix evenly. Then, add component (D) thermal conductive filler into the kettle, mix evenly, heat to 80 to 150°C, maintain positive pressure and high temperature treatment for 2 to 6 hours, and then vacuum and stir at 100 to 150°C for 1 to 3 hours to obtain the thermal conductive filler pretreatment product. Among them, the amount of ethanol solution of deionized water added needs to be adjusted according to the amount of hydroxyl content on the surface of the thermal conductive filler, generally 0.1 to 5 times of the reactive siloxy-terminated polymer (RST) of component (C).
[0023] After cooling the thermally conductive filler pretreatment material to below 40°C, component (E) cyclic polysiloxane adhesion promoter and component (F) platinum catalyst are added. Due to the need for operation time, a suitable inhibitor can be appropriately added. After mixing and stirring evenly, component (B) organic siloxane polymer having 2 or more Si-H bonds per molecule is added. After fully stirring evenly, a high-toughness thermally conductive structure bonding organic polysiloxane composition is obtained.
[0024] The beneficial effects of this preparation process are: pre-treating the thermally conductive filler in advance increases the interfacial compatibility of organic and inorganic materials, which is more conducive to reducing the overall viscosity of the product system, and at the same time helps to form a chemical bond that tightly binds component (C) to the interface of the thermally conductive filler, which is more conducive to the toughening of the final product. At the same time, we found in our research that a positive pressure treatment temperature of 80 to 150°C is necessary, and a lower treatment temperature is not conducive to improving the product's high temperature and high humidity resistance. Secondly, component (E) cyclic polysiloxane adhesion promoter must be added later and cannot be added during filler pretreatment, not only to prevent the formation of a bonding competition relationship with component (C) on the filler surface, but if component (E) is added during filler pretreatment, the high temperature and high humidity resistance of the product will be reduced.
[0025] Based on this patent invention, adjustments can be made to meet the corresponding application requirements: such as adding fluorescent agents to provide fluorescence detection capabilities, adding color pastes and carbon black to adjust the appearance color, adding fumed silica and thixotropic additives to adjust the rheological properties, etc.
[0026] The present invention provides a high-toughness thermal conductive structure bonding organic polysiloxane composition and a preparation method thereof, which is suitable for thermal management system bonding applications requiring high toughness, high thermal conductivity and high reliability, such as integrated circuit packaging chip heat dissipation frame bonding, etc. The beneficial effects of the present invention are as follows: the present invention adopts reactive siloxy-terminated polymer (RST) and cyclic polysiloxane adhesion promoter as a treatment agent for thermal conductive fillers and a promoter for interfacial bonding, respectively. On the one hand, the functions of traditional thermal conductive filler treatment agents and interfacial bonding promoters can be realized: increasing the interfacial compatibility of organic and inorganic materials, reducing viscosity and promoting interfacial bonding; on the other hand, these two major components can participate in the formation of a cross-linked network of the overall organic material, so that the inorganic filler and the annular structure effectively become a reinforcing and toughening structure of the composite material, which is helpful for the mechanical toughening of the composite material. The present invention discloses a suitable treatment process for thermal conductive fillers and a preparation method for the composition, which helps RST to form a close chemical reaction with the thermal conductive filler, and effectively improves the high temperature and high humidity resistance of the composite material. Specific implementation method:
[0027] The following specific embodiments describe the principles and features of the present invention. The examples are only used to explain the present invention and are not used to limit the scope of the present invention.
[0028] Example 1
[0029] Weigh 15 parts (Vi(CH 3 ) 2 SiO 1 / 2 )((CH 3 ) 2 SiO 2 / 2 ) 60 (Vi represents vinyl), 2 parts (Vi(CH 3 ) 2 SiO 1 / 2 ) 0.2 ((CH 3 ) 3 SiO 1 / 2 ) 0.8 (SiO 4 / 2 ) 1.2 , 0.5 parts of reactive siloxy-terminated polymer (RST-1, the structural formula is as follows), after mixing and stirring evenly, add 0.2 parts of ethanol solution of deionized water (the content of deionized water is 5‰), and stir and mix evenly. Subsequently, add 60.45 parts of spherical alumina with an average particle size of 30um and 20 parts of aluminum nitride with an average particle size of 5um into the kettle, mix evenly, heat to 100°C, maintain positive pressure and high temperature treatment for 3h, and then vacuum and stir at 120°C for 1h to obtain the thermal conductive filler pretreatment.
[0030]
[0031] After cooling the thermally conductive filler pretreatment to below 40°C, add 0.5 parts of (E) cyclic polysiloxane adhesion promoter-1 (structural formula as follows) and 0.05 parts of a 5000 ppm platinum capsule platinum catalyst, mix and stir evenly, then add 1.5 parts of (CH 3 ) 3 SiO 1 / 2 ((CH 3 )HSiO 2 / 2 ) 10 ((CH 3 ) 2 SiO 2 / 2 ) 25 After being fully stirred, a high-toughness thermal conductive structural bonding organic polysiloxane composition is obtained.
[0032]
[0033] Example 2
[0034] Weigh 18.85 parts (Vi(CH 3 ) 2 SiO 1 / 2 )((CH 3 ) 2 SiO 2 / 2 ) 30 ((CH 3 ) 2 SiO 3 / 2 ) 1 (Vi represents vinyl), 0.2 parts of reactive siloxy-terminated polymer (RST-2, the structural formula is as follows), after mixing and stirring evenly, add 0.2 parts of ethanol solution of deionized water (the content of deionized water is 1‰), and stir and mix evenly. Subsequently, add 74 parts of aluminum hydroxide with an average particle size of 20um into the kettle, mix evenly, heat to 80°C, maintain positive pressure and high temperature treatment for 6 hours, and then vacuum and stir at 120°C for 1 hour to obtain a thermal conductive filler pretreatment.
[0035]
[0036] After cooling the thermal conductive filler pretreatment to below 40°C, add 1.0 part (E) cyclic polysiloxane adhesion promoter-2 (structural formula as follows), 0.05 part 5000ppm platinum-vinylsiloxane complex and 0.05 part methyl butynol, mix and stir evenly, then add 0.8 part (CH 3 ) 2 HSiO 1 / 2 (SiO 4 / 2 ) 0.8 and 5.0 parts (CH 3 ) 2HSiO 1 / 2 ((CH 3 ) 2 SiO 2 / 2 ) 20 After being fully stirred, a high-toughness thermal conductive structural bonding organic polysiloxane composition is obtained.
[0037]
[0038] Example 3
[0039] Weigh 7.5 parts (Vi(CH 3 ) 2 SiO 1 / 2 )((CH 3 ) 2 SiO 2 / 2 ) 150 (Vi(CH 3 ) 2 SiO 2 / 2 ) 10 (Vi represents vinyl), 2 parts (Vi(CH 3 ) 2 SiO 1 / 2 )((CH 3 ) 2 SiO 2 / 2 ) 30 , 3 parts of reactive silaneoxy terminated polymer (RST-3, the structural formula is as follows), after mixing and stirring evenly, add 0.3 parts of ethanol solution of deionized water (the content of deionized water is 5‰), and stir and mix evenly. Subsequently, add 20 parts of zinc oxide with an average particle size of 1um, 20 parts of aluminum nitride with an average particle size of 5um, and 45 parts of aluminum powder with an average particle size of 8um into the kettle, mix evenly, heat to 120℃, maintain positive pressure high temperature treatment for 3h, and then vacuum and stir at 150℃ for 3h to obtain the thermal conductive filler pretreatment.
[0040]
[0041] After cooling the thermal conductive filler pretreatment to below 40°C, add 0.3 parts of (E) cyclic polysiloxane adhesion promoter-3 (structural formula as follows), 0.1 parts of 1-ethynyl-1-cyclohexanol and 0.2 parts of 2000ppm platinum-vinylsiloxane complex, mix and stir evenly, then add 1.9 parts of (CH 3 ) 2 HSiO 1 / 2 ((CH 3 ) 2 SiO 2 / 2 ) 7 ((CH 3 )HSiO 2 / 2 )1 (CH 3 SiO 3 / 2 ), and after being fully stirred, a high-toughness thermal conductive structure bonding organic polysiloxane composition is obtained.
[0042]
[0043] Example 4
[0044] Weigh 20 parts (Vi(CH 3 ) 2 SiO 1 / 2 )((CH 3 ) 2 SiO 2 / 2 ) 60 (Vi represents vinyl), 10.9 parts (Vi(CH 3 ) 2 SiO 1 / 2 ) 0.2 ((CH 3 ) 3 SiO 1 / 2 ) 0.8 (SiO 4 / 2 ) 1.2 , 1 part of reactive silaneoxy terminated polymer (RST-4, the structural formula is as follows), after mixing and stirring evenly, add 4 parts of ethanol solution of deionized water (the content of deionized water is 1‰), and stir and mix evenly. Subsequently, add 60 parts of alumina with an average particle size of 10um into the kettle, mix evenly, heat to 100℃, maintain positive pressure and high temperature treatment for 3h, and then vacuum and stir at 120℃ for 1h to obtain the thermal conductive filler pretreatment.
[0045]
[0046] After cooling the thermal conductive filler pretreatment to below 40°C, add 1.8 parts of (E) cyclic polysiloxane adhesion promoter-4 (structural formula as follows) and 0.8 parts of a capsule platinum catalyst with a platinum content of 1000 ppm, mix and stir evenly, then add 4 parts of (CH 3 ) 2 HSiO 1 / 2 (SiO 4 / 2 ) 0.8 and 1.5 parts (CH 3 ) 2 HSiO 1 / 2 ((CH 3 ) 2 SiO 2 / 2 ) 20 After being fully stirred, a high-toughness thermal conductive structural bonding organic polysiloxane composition is obtained.
[0047]
[0048] Comparative Example 1
[0049] Weigh 15 parts (Vi(CH 3 ) 2 SiO 1 / 2 )((CH 3 ) 2 SiO 2 / 2 ) 60 (Vi represents vinyl), 2 parts (Vi(CH 3 ) 2 SiO 1 / 2 ) 0.2 ((CH 3 ) 3 SiO 1 / 2 ) 0.8 (SiO 4 / 2 ) 1.2 , 0.5 parts of reactive siloxy-terminated polymer (RST-1), after mixing and stirring evenly, add 0.2 parts of ethanol solution of deionized water (the content of deionized water is 5‰), and stir and mix evenly. Subsequently, add 60.45 parts of spherical alumina with an average particle size of 30um and 20 parts of aluminum nitride with an average particle size of 5um into the kettle, mix evenly, heat to 60°C, maintain positive pressure and high temperature treatment for 3h, and then vacuum and stir at 120°C for 1h to obtain the thermal conductive filler pretreatment.
[0050] After cooling the thermally conductive filler pretreatment to below 40°C, add 0.5 parts of (E) cyclic polysiloxane adhesion promoter-1 and 0.05 parts of a 5000 ppm platinum capsule platinum catalyst, mix and stir evenly, then add 1.5 parts of (CH 3 ) 3 SiO 1 / 2 ((CH 3 )HSiO 2 / 2 ) 10 ((CH 3 ) 2 SiO 2 / 2 ) 25 After being fully stirred, a high-toughness thermal conductive structural bonding organic polysiloxane composition is obtained.
[0051] Comparative Example 2
[0052] Weigh 15 parts (Vi(CH 3 ) 2 SiO 1 / 2 )((CH 3 ) 2 SiO 2 / 2 ) 60(Vi represents vinyl), 2 parts (Vi(CH 3 ) 2 SiO 1 / 2 ) 0.2 ((CH 3 ) 3 SiO 1 / 2 ) 0.8 (SiO 4 / 2 ) 1.2 , 0.5 parts of silaneoxy-terminated polymer (structural formula as follows), after mixing and stirring evenly, add 0.2 parts of ethanol solution of deionized water (the content of deionized water is 5‰), and stir and mix evenly. Subsequently, add 60.45 parts of spherical alumina with an average particle size of 30um and 20 parts of aluminum nitride with an average particle size of 5um into the kettle, mix evenly, heat to 100°C, maintain positive pressure and high temperature treatment for 3h, and then vacuum and stir at 120°C for 1h to obtain the thermal conductive filler pretreatment.
[0053]
[0054] After cooling the thermally conductive filler pretreatment to below 40°C, add 0.5 parts of (E) cyclic polysiloxane adhesion promoter-1 and 0.05 parts of a 5000 ppm platinum capsule platinum catalyst, mix and stir evenly, then add 1.5 parts of (CH 3 ) 3 SiO 1 / 2 ((CH 3 )HSiO 2 / 2 ) 10 ((CH 3 ) 2 SiO 2 / 2 ) 25 After being fully stirred, a high-toughness thermal conductive structural bonding organic polysiloxane composition is obtained.
[0055] Comparative Example 3
[0056] Weigh 18.85 parts (Vi(CH 3 ) 2 SiO 1 / 2 )((CH 3 ) 2 SiO 2 / 2 ) 30 ((CH 3 ) 2 SiO 3 / 2 ) 1(Vi represents vinyl), 0.2 parts of reactive siloxy-terminated polymer (RST-2, the structural formula is as follows), after mixing and stirring evenly, add 0.1 parts of ethanol solution of deionized water (the content of deionized water is 1‰), and stir and mix evenly. Subsequently, add 74 parts of aluminum hydroxide with an average particle size of 20um into the kettle, mix evenly, heat to 80°C, maintain positive pressure and high temperature treatment for 6 hours, and then vacuum and stir at 120°C for 1 hour to obtain the thermal conductive filler pretreatment.
[0057]
[0058] After cooling the thermal conductive filler pretreatment to below 40°C, add 1.0 part of polysiloxane adhesion promoter (structural formula as follows), 0.05 part of 5000ppm platinum-vinylsiloxane complex and 0.05 part of methyl butynol, mix and stir evenly, then add 0.8 part of (CH 3 ) 2 HSiO 1 / 2 (SiO 4 / 2 ) 0.8 and 5.0 parts (CH 3 ) 2 HSiO 1 / 2 ((CH 3 ) 2 SiO 2 / 2 ) 20 After being fully stirred, a high-toughness thermal conductive structural bonding organic polysiloxane composition is obtained.
[0059]
[0060] Comparative Example 4
[0061] Weigh 7.5 parts (Vi(CH 3 ) 2 SiO 1 / 2 )((CH 3 ) 2 SiO 2 / 2 ) 150 (Vi(CH 3 ) 2 SiO 2 / 2 ) 10 (Vi represents vinyl), 2 parts (Vi(CH 3 ) 2 SiO 1 / 2 )((CH 3 ) 2 SiO 2 / 2 ) 30, 3 parts of reactive silaneoxy terminated polymer (RST-3), and 0.3 parts of (E) cyclic polysiloxane adhesion promoter-3, after mixing and stirring evenly, add 0.3 parts of deionized water ethanol solution (the content of deionized water is 5‰), and stir and mix evenly. Subsequently, add 20 parts of zinc oxide with an average particle size of 1um, 20 parts of aluminum nitride with an average particle size of 5um, and 45 parts of aluminum powder with an average particle size of 8um into the kettle, mix evenly, heat to 120℃, maintain positive pressure high temperature treatment for 3h, and then vacuum and stir at 150℃ for 3h to obtain the thermal conductive filler pretreatment.
[0062]
[0063] After cooling the thermal conductive filler pretreatment to below 40°C, add 0.1 parts of 1-ethynyl-1-cyclohexanol and 0.2 parts of 2000ppm platinum-vinylsiloxane complex, mix and stir evenly, then add 1.9 parts of (CH 3 ) 2 HSiO 1 / 2 ((CH 3 ) 2 SiO 2 / 2 ) 7 ((CH 3 )HSiO 2 / 2 ) 1 (CH 3 SiO 3 / 2 ), and after being fully stirred, a high-toughness thermal conductive structure bonding organic polysiloxane composition is obtained.
[0064] The test items and test conditions are as follows:
[0065] 1. Thermal curing conditions: 150℃*1h;
[0066] 2.Tensile strength and elongation at break tests shall be conducted in accordance with GB / T528-2009;
[0067] 3. Lap shear strength test, the overlap area is (25±0.25)mm*(12.5±0.25)mm, and the thickness is 0.15mm;
[0068] 4.The thermal conductivity test instrument is: Hot DISC thermal conductivity instrument;
[0069] 5.UHAST aging test conditions: 130℃*85RH%*1atm;
[0070] Table 1 Summary of test results after preparation of the embodiments and comparative examples
[0071]
[0072] As can be seen from Table 1, after being cured at 150°C*1h, the high-toughness thermally conductive structural adhesive organopolysiloxane composition of the present invention has a bulk strength of more than 2MPa while having a thermal conductive function, and even when the thermal conductivity reaches 3MPa W / mk, it still has an elongation of 30%, and has high toughness. After being aged under UHAST 192h, the tensile strength, elongation at break, and lap shear strength all decrease very little, and can meet the bonding application of thermal management systems that require high toughness, high thermal conductivity, and high reliability.
[0073] Compared with Example 1, when the temperature of powder treatment is low, it is not conducive to the close chemical reaction between RST and thermal conductive filler. Although the initial performance after curing is not greatly affected, after aging under high temperature, high humidity and high pressure reliability conditions, the elongation decreases significantly.
[0074] Compared with Example 1, the powder treatment agent used in Comparative Example 2 does not contain a reaction functional group for addition curing, so that the powder treatment agent and the powder particles are components independent of the cross-linked network and cannot interact with the cross-linked network, thus failing to achieve the effect of reinforcement and toughening, and the tensile strength, elongation at break and lap shear strength all show a significant decrease;
[0075] Compared with Example 2, Comparative Example 3 uses a non-annular polysiloxane adhesion promoter to replace the polysiloxane adhesion promoter containing an annular structure, and the tensile strength and elongation at break both decrease slightly, indicating that the easily deformable annular structure in the adhesion promoter helps to form a linkage effect, thereby helping to improve the strength and elongation of the entire system;
[0076] Comparative Example 4 Compared with Example 3, the cyclic polysiloxane adhesion promoter and the powder treatment agent RST are added simultaneously. The tensile strength and elongation at break after curing are not much different, and are basically the same, but the lap shear strength of Comparative Example 4 is lower. In addition, after high temperature, high pressure, and high humidity aging, the elongation at break and the lap shear strength decrease more greatly, and the lap shear strength. It shows that the simultaneous addition of the cyclic polysiloxane adhesion promoter and the powder treatment agent RST is likely to cause a competitive bonding relationship on the surface of the filler. On the one hand, it makes the powder coating poor, which is easy to make the high temperature and high humidity resistance effect poor. On the other hand, it also consumes the active bonding groups of the adhesion promoter, resulting in poor interface bonding. After aging, it is more susceptible to erosion and causes interface bonding damage, thereby significantly reducing the bonding strength.
Claims
1. A high-toughness thermally conductive structural adhesive organic polysiloxane composition comprises at least the following components (A)-(F) in parts by weight: (A) 5-35 parts of an organic siloxane polymer having 2 or more alkenyl groups per molecule; (B) 0.1-10 parts of an organic siloxane polymer having 2 or more Si-H bonds per molecule; (C) 0.05-5 parts of a reactive siloxy-terminated polymer; (D) 55-95 parts of a thermally conductive filler; (E) 0.05-2 parts of a cyclic polysiloxane adhesion promoter; and (F) 0.01-1 parts of a platinum catalyst.
2. The high-toughness thermally conductive structure bonding organopolysiloxane composition according to claim 1, characterized in that: The component (A) is an organosiloxane polymer having 2 or more alkenyl groups per molecule, and its general structural formula is (R 1 R 2 2SiO 1 / 2 )(R 1 R 2 SiO 2 / 2 ) a (R 2 SiO 3 / 2 ) b (SiO 4 / 2 ) c ; Among them, R 1 , R 2 are one of methyl, ethyl, vinyl, and phenyl, and R 1 and R 2 One or two of the groups are vinyl groups; a = 0~180 (excluding 0), b = 0~2, c = 0~2, a+b+c = 1~180.
3. The high-toughness thermally conductive structure bonding organopolysiloxane composition according to claim 1, characterized in that: The component (B) is an organosiloxane polymer having 2 or more Si-H bonds per molecule, and its general structural formula is (R 1 R 2 2SiO 1 / 2 )(R 1 R 2 SiO 2 / 2 ) m (R 2 SiO 3 / 2 ) n (SiO 4 / 2 ) x , where R 1 , R 2 are methyl, ethyl, or phenyl, and R 1 and R 2 One or two of the groups are H groups; m = 0~35, n = 0~2, c = 0~0.5, m+n+c = 1~35.
4. The high-toughness thermally conductive structure bonding organopolysiloxane composition according to claim 1, characterized in that: The component (C) is a reactive siloxy-terminated polymer, and its structure is as follows: Among them, R 1 , R 2 R3 is vinyl, propenyl or H group; y1, y2, y3, y4 are integers, and y1+y2+y3+y4= 0-50.
5. The high-toughness thermally conductive structure bonding organopolysiloxane composition according to claim 1, characterized in that: The thermal conductive filler of component (D) is one or more of aluminum oxide, aluminum hydroxide, aluminum nitride, and aluminum powder, and the particle size of the thermal conductive filler is less than or equal to 80 um.
6. The high-toughness thermally conductive structure bonding organopolysiloxane composition according to claim 1, characterized in that: The component (E) cyclic polysiloxane adhesion promoter is a ring body with 4-8 Si-O segments, the side group on one side of the Si atom is one of methyl, ethyl, propyl, and isopropyl, and the side group on the other side contains one of siloxane group, epoxy group, acyloxy group, methyl, ethyl, propyl, isopropyl, vinyl, propenyl, and H; the cyclic polysiloxane adhesion promoter molecule contains 2 or more siloxane groups, epoxy groups, and acyloxy groups, and contains 1 or more vinyl, propenyl, and H groups.
7. The high-toughness thermally conductive structure bonding organopolysiloxane composition according to claim 1, characterized in that: The platinum catalyst of component (F) is one or a mixture of platinum chloride, alcohol-modified platinum chloride, a complex of platinum chloride and diene, a platinum-olefin complex, a platinum-carbonyl complex such as platinum bis(acetoacetate) or platinum bis(acetylacetone), a platinum chloride-alkenylsiloxane complex such as platinum chloride-divinyltetramethyldisiloxane complex or platinum chloride-tetravinyltetramethylcyclotetrasiloxane, a platinum-alkenylsiloxane complex such as platinum-divinyltetramethyldisiloxane complex or platinum-tetravinyltetramethylcyclotetrasiloxane, a complex between platinum chloride and acetylene alcohol, and a capsule-type platinum catalyst.
Citation Information
Patent Citations
Organopolysiloxane composition with excellent adhesion and reliability and preparation method thereof
CN114058326A
Two-component silicone structural sealant as well as preparation system and preparation method thereof
CN115322737A
Thermo-conductive silicone potting composition
JP2016084378A
Cited By
Organic silicon heat-conducting composite material and preparation method thereof
CN121592188A
